Analysis and research of quadruped robot's legs: A comprehensive review. (2nd May 2019) - Zhong, Yuhai; Wang, Runxiao; Feng, Huashan; Chen, Yasheng
As an important basic component of quadruped robots, mechanical legs provide the robots with excellent maneuverability and versatility, which determine the core application performance such as job adaptability, walking speed, and load capacity. A large number of robotics institutes for the last few decades have studied mechanical legs used by quadruped robots and published many research results. In this article, we collect these research results and classify them into three categories (prismatic legs, articulated legs, and redundant articulated legs) according to the degrees of freedom and then introduce and analyze them. On this basis, we summarize and study the design methods of the actuators and mechanical leg structures. Finally, we make some suggestions for the development of quadruped robot's legs in the future. The motivation of this review is to summarize and analyze previous research efforts and provide useful guidance for future robotic designers to develop more efficient mechanical legs of quadruped robots.